Attempting genetic inference from directional asymmetry during convergent hindlimb reduction in squamates. Issue 7 (14th July 2022) - Swank, Samantha; Elazegui, Ethan; Janidlo, Sophia; Sanger, Thomas J.; Bell, Michael A.; Stuart, Yoel E.
Abstract: Loss and reduction in paired appendages are common in vertebrate evolution. How often does such convergent evolution depend on similar developmental and genetic pathways? For example, many populations of the threespine stickleback and ninespine stickleback (Gasterosteidae) have independently evolved pelvic reduction, usually based on independent mutations that caused reduced Pitx1 expression. Reduced Pitx1 expression has also been implicated in pelvic reduction in manatees. Thus, hindlimb reduction stemming from reduced Pitx1 expression has arisen independently in groups that diverged tens to hundreds of millions of years ago, suggesting a potential for repeated use of Pitx1 across vertebrates. Notably, hindlimb reduction based on the reduction in Pitx1 expression produces left‐larger directional asymmetry in the vestiges. We used this phenotypic signature as a genetic proxy, testing for hindlimb directional asymmetry in six genera of squamate reptiles that independently evolved hindlimb reduction and for which genetic and developmental tools are not yet developed: Agamodon anguliceps, Bachia intermedia, Chalcides sepsoides, Indotyphlops braminus, Ophisaurus attenuatuas and O. ventralis, and Teius teyou . Significant asymmetry occurred in one taxon, Chalcides sepsoides, whose left‐side pelvis and femur vestiges were 18% and 64% larger than right‐side vestiges, respectively, suggesting modification in Pitx1 expression in that species . However, there was either right‐larger asymmetry or no directional asymmetry in the other five taxa, suggesting multiple developmental genetic pathways to hindlimb reduction in squamates and the vertebrates more generally. Abstract : We quantified directional asymmetry in the vestigial hindlimbs of six squamate lineages to test for parallel loss of gene expression of Pitx1 during convergent limb reduction. We found left‐larger asymmetry in one of six taxa, suggesting that Pitx1 may be involved in that lineage. However, it is likely that non‐parallel genetic mechanisms underlie pelvic reduction in the squamates.